1999
DOI: 10.1677/joe.0.1610025
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the colon on postprandial glucagon-like peptide 1 (7-36) amide concentration in man

Abstract: Glucagon-like peptide (7-36) amide (GLP-1) is an incretin hormone of the enteroinsular axis released rapidly after meals despite the fact that GLP-1 secreting cells (L-cells) occur predominantly in the distal gut. The importance of these colonic L-cells for postprandial GLP-1 was determined in healthy control subjects and in ileostomy patients with minimal small bowel resection (<5 cm). Subjects were fed a high complex carbohydrate test meal (15·3 g starch) followed by two carbohydratefree, high fat test meals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…This tallies well with both an observed reduction in hepatic glucose production 12 h after insoluble fibre ingestion [25] and the high amounts of liver glycogen found in rats adapted to a high-RS diet [39]. The colon is an important site for luminal and neurally-stimulated GLP-1 release [40]. GLP-1 has been strongly implicated in postprandial oral glucose tolerance, stimulating insulin release and having independent insulinotropic effects [41].…”
Section: Discussionsupporting
confidence: 65%
“…This tallies well with both an observed reduction in hepatic glucose production 12 h after insoluble fibre ingestion [25] and the high amounts of liver glycogen found in rats adapted to a high-RS diet [39]. The colon is an important site for luminal and neurally-stimulated GLP-1 release [40]. GLP-1 has been strongly implicated in postprandial oral glucose tolerance, stimulating insulin release and having independent insulinotropic effects [41].…”
Section: Discussionsupporting
confidence: 65%
“…Generally, there is little information on GLP-1 release in IBD patients, so far (7,41,49). In particular, to our knowledge, GLP-1 responses to a normal, mixed meal in noncolectomized patients with UC and in patients with CD have not been studied before.…”
Section: Discussionmentioning
confidence: 99%
“…Third, autonomic neuropathy (10,16,54) and alterations of intramural neurons (9,28,40,45) have been observed in IBD and might disturb gastrointestinal motility. Finally, there is evidence that release of several gastrointestinal neurohormonal mediators that regulate gastric functions may be altered in IBD (1,7,49,58,59); however, these results were conflicting, and roles of key regulators, particularly CCK, peptide YY (PYY), and glucagon-like peptide-1 (GLP-1) (51) have remained unclear. Disturbed release of gastrointestinal hormones from the inflamed mucosa might also contribute to gastric emptying disturbances in diverticulitis, but no systematic studies have been reported.…”
mentioning
confidence: 99%
“…In human subjects with ileostomies, the circulating GLP-1 levels after a fat load are significantly reduced compared with healthy control subjects, suggesting that loss of colonic endocrine tissue is an important determinant in regulating postprandial GLP-1 levels (72). In vivo studies of rodents and humans have shown that increased SCFA production after dietary fiber ingestion increases GLP-1 levels (19,70,97).…”
Section: E656mentioning
confidence: 99%